Metabolic acidosis is common and associates with disease progression in children with chronic kidney disease - ALPAY, HARİKA (ELSEVIER SCIENCE INC, 2017)
Recent studies in adult chronic kidney disease (CKD) suggest that metabolic acidosis is associated with faster decline in estimated glomerular filtration rate (eGFR). Alkali therapies improve the course of kidney disease. Here we investigated the prevalence and determinants of abnormal serum bicarbonate values and whether metabolic acidosis may be deleterious to children with CKD. Associations between follow-up serum bicarbonate levels categorized as under 18, 18 to under 22, and 22 or more mmol/l and CKD outcomes in 704 children in the Cardiovascular Comorbidity in Children with CKD Study, a prospective cohort of pediatric patients with CKD stages 3-5, were studied. The eGFR and serum bicarbonate were measured every six months. At baseline, the median eGFR was 27 ml/min/1.73m(2) and median serum bicarbonate level 21 mmol/l. During a median follow-up of 3.3 years, the prevalence of metabolic acidosis (serum bicarbonate under 22 mmol/l) was 43%, 60%, and 45% in CKD stages 3, 4, and 5, respectively. In multivariable analysis, the presence of metabolic acidosis as a time-varying covariate was significantly associated with log serum parathyroid hormone through the entire follow-up, but no association with longitudinal growth was found. A total of 211 patients reached the composite endpoint (ESRD or 50% decline in eGFR). In a multivariable Cox model, children with time-varying serum bicarbonate under 18 mmol/l had a significantly higher risk of CKD progression compared to those with a serum bicarbonate of 22 or more mmol/l (adjusted hazard ratio 2.44; 95% confidence interval 1.43-4.15). Thus, metabolic acidosis is a common complication in pediatric patients with CKD and may be a risk factor for secondary hyperparathyroidism and kidney disease progression.
Keywords: children; chronic kidney disease; metabolic acidosis; progression; outcome; GLOMERULAR-FILTRATION-RATE; LONG-TERM OUTCOMES; SERUM BICARBONATE; TUBULAR-ACIDOSIS; CKD; DECLINE; GROWTH; GFR; INFLAMMATION; PREVALENCE